The Tendencies of the Education of Humanity in Lithuania at the End of the 19th- the Middle of the 20th Century - Bakutytė, Rima (Acta Paedagogica Vilnensia, 1997)
This article presents the tendencies of the education of humanity at the end of the XIX – the middle of the XX century. Attention is paid to the common peculiarities of the pedagogical research of this period. This clears up some authors' attitudes towards the content, place, and significance of humanity, tries to disclose some reflections of moral principles, and discusses the main factors, means and methods that could exist even today.
Keywords: history of education; humanity; education of humanity; moral education; methods in education